THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL CAPABILITY, DIGITAL SERVICE TAX (DST) AND LIFESTYLE ON CONSUMPTIVE BEHAVIOR IN ONLINE SHOPPING VIA THE TIKTOK SHOP PLATFORM - Islamiah Kamil; Ariani, Meiliyah; Indra Ade Irawan; Sri Anjarwati; Yolifiandri; Zulhawati (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Consumer behavior in online shopping via the TikTok Shop platform is an interesting phenomenon in the current digital era. This research aims to analyze and measure the influence of financial literacy, financial ability, application of Digital Service Tax (DST), and lifestyle on consumer behavior when shopping online via the Tiktok Shop platform. This research uses a theoretical framework that includes financial literacy, financial capabilities, digital consumer behavior theory, and the AIDA model to analyze the factors that influence online shopping consumer behavior via the Tiktok Shop platform. The research sample consisted of 300 users of the Tiktok Shop platform in the Jabodetabek area (Jakarta, Bogor, Depok, Tangerang and Bekasi). Primary data was collected using a questionnaire. The analytical method used to test the hypothesis is Regression Analysis with SMART PLS. The results of this research are that the financial literacy variable influences consumer behavior when shopping online via the Tiktok Shop platform, while the other three variables, namely financial ability, application of Digital Service Tax (DST), and lifestyle, do not influence consumer behavior when shopping online via the Tiktok Shop platform. It is hoped that the findings of this research will provide deeper insight into the factors that influence consumer behavior when shopping online through TikTok Shop and the implications for practical digital marketing and tax policy.